The Influence of Corporate Governance On the Financial Performance of Mining Companies Listed on the BEI - Annisa Rahim; Teti Chandrayanti; Rizka Hadya (Fakultas Ekonomi, Universitas Ekasakti, 2024)
Investors are more aware that good corporate governance is no longer just an option, it is actually a necessity to achieve sustainable corporate financial performance. This study aims to examine the influence of corporate governance in institutional ownership(1), managerial ownership(2), board of commissioners(3), and audit committee(4) either partially or simultaneously on financial performance as measured by Return on Equity (ROE). Data processing using a Multiple Linear Regression Model which is based on secondary data from the company's annual report and financial reports. The population of this research is 87 mining companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample was selected based on the purposive sampling method totaling 14 companies. The results of the regression analysis show that partially the institutional ownership variable (X1) has a negative but not significant effect on ROE, managerial ownership (X2) has a positive but not significant effect on ROE financial performance, the board of commissioners (X3) has a positive and significant effect on ROE financial performance, Audit committee (X4) has a positive but not significant effect on ROE financial performance. Simultaneously institutional ownership, managerial ownership, board of commissioners and audit committee have a positive and significant effect on ROE financial performance.